Investigation of the Lactic Acid Bacteria in Kazak Cheese and Their Contributions to Cheese Fermentation - Li, Jie; Huang, Qian; Zheng, Xiaochun; Ge, Zhengkai; Lin, Ke; Zhang, Dandan; Chen, Yu; Wang, Bin; Shi, Xuewei (Frontiers in Microbiology, 2020)
Abstract: Kazak cheese is a traditional dairy product fermented by lactic acid bacteria in Xinjiang. To investigate the core lactic acid bacteria in Kazak cheese and their contributions to cheese fermentation, four representative core lactic acid bacteria, Streptococcus thermophilus B8, Lactobacillus helveticus B6, Weissella confusa B14 and Lactobacillus rhamnosus B10 were isolated from Kazak cheese and subsequently used to ferment cheeses, which were named StC, LhC, WcC and LrC, respectively. The changes in the proteins, amino acids, organic acids, texture, volatile compounds and physical and chemical indicators of the cheeses were investigated. Most of the physical and chemical indicators, except for moisture and fat, of the cheeses produced by different bacteria were not significantly different. All of the cheeses, StC, LhC, WcC and LrC, contained high levels of Glu and tartaric acid. W. confusa B14 and S. thermophilus B8 produced high concentrations of amino acids and organic acids, respectively. S. thermophilus B8 also produced cheese with ideal texture properties, including high levels of springiness, cohesiveness, chewiness, gumminess and chewiness resilience. Furthermore, the selected lactic acid bacteria generated cheeses with unique flavors. LrC, StC and WcC exhibited a sour and fruity aroma, while LhC had a strong sour aroma. This is because L. rhamnosus B10 produced a high concentration of acetic acid, 3-methylbutanoic acid, 2-methylpentanoic acid, hexanoic acid, isoamyl acetate and ethyl caprylate in LrC. S. thermophilus B8 contributed to the formation of ethanol, acetic acid, 3-methylbutanoic acid, hexanoic acid and isoamyl acetate. W. confusa B14 yielded a large amount of isoamylol, acetic acid, 3-methylbutanoic acid, ethyl acetate and isoamyl acetate. However, L. helveticus B6 promoted the formation of only acetic acid and isoamyl acetate (up to 5%). This study will provide a theoretical basis for the quality control and industrial production of Kazak cheese.